The relationship of weld metal hardness residual stress and susceptible to stress corrosion cracking in hydrogen sulphide environment in A516 Grade 70 carbon steel shielded metal arc welded joint - Pistorius, Pieter Georg Hendrik (University of Pretoria, 2019)
Dissertation (MEng)--University of Pretoria, 2017.